St. John’s Wort inhibits insulin signaling in murine and human adipocytes - Richard, Allison J. (2011)
Adipocytes are insulin-sensitive cells that play a major role in energy homeostasis. Obesity is the primary disease of fat cells and a major risk factor for the development of Type 2 diabetes, cardiovascular disease, and metabolic syndrome. The use of botanicals in the treatment of metabolic diseases is an emerging area of research. In previous studies, we screened over 425 botanical extracts for their ability to modulate adipogenesis and insulin sensitivity. We identified St. John’s Wort (SJW) extracts as inhibitors of adipogenesis of 3T3-L1 cells and demonstrated that these extracts also inhibited insulin-sensitive glucose uptake in mature fat cells. In these follow-up studies we have further characterized the effects of SJW on insulin action in both murine and human fat cells. We have shown that SJW also attenuates insulin-sensitive glucose uptake in human adipocytes. Moreover, SJW inhibits IRS-1 tyrosine phosphorylation in both murine and human fat cells. Botanical extracts are complex mixtures. Many bioactive compounds have been identified in SJW, including hypericin (HI) and hyperforin (HF). We have examined the ability of HI and HF, purified from SJW, to modulate adipocyte development and insulin action in mature adipocytes. Our novel studies indicate that the profound effects of SJW on adipogenesis, IRS-1 activation, and insulin-stimulated glucose uptake are not mediated by HI and/or HF. Nonetheless, we propose that extracts of SJW may contribute to adipocyte related diseases by limiting differentiation of preadipocytes and significantly inducing insulin resistance in mature fat cells.